2010
DOI: 10.1145/1857920.1857924
|View full text |Cite
|
Sign up to set email alerts
|

Usability of a Multimodal Video Game to Improve Navigation Skills for Blind Children

Abstract: This work presents an evaluative study on the usability of a haptic device together with a sound-based video game for the development and use of orientation and mobility (O&M) skills in closed, unfamiliar spaces by blind, school-aged children. A usability evaluation was implemented for a haptic device especially designed for this study (Digital Clock Carpet) and a 3D video game (MOVA3D) in order to determine the degree to which the user accepted the device, and the level of the user’s satisfaction regardin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(18 citation statements)
references
References 25 publications
0
17
0
1
Order By: Relevance
“…Esta indagación permite a los autores de este escrito visualizar que las definiciones respecto a los videojuegos provienen de áreas tales como la educación (Grupo F9, 2000;Gómez et al, 2003;Mendiz et al, 2003;Pérez et al, 2003;De Aguilera & Mañas, 2001;De Aguilera & Mendiz, 2003;Sánchez et al, 2010) la ludología (Aarseth, 1997) y la informática (Nussbaum et al, 2003), entre otras; no obstante, no se evidencia una construcción teórica que asuma al videojuego como un discurso, es decir, que provenga desde el ámbito de la lingüística y desde una perspectiva multimodal. Knight (2015).…”
Section: Videojuego Como Discurso Digital: Aspectos Metodológicos Parunclassified
“…Esta indagación permite a los autores de este escrito visualizar que las definiciones respecto a los videojuegos provienen de áreas tales como la educación (Grupo F9, 2000;Gómez et al, 2003;Mendiz et al, 2003;Pérez et al, 2003;De Aguilera & Mañas, 2001;De Aguilera & Mendiz, 2003;Sánchez et al, 2010) la ludología (Aarseth, 1997) y la informática (Nussbaum et al, 2003), entre otras; no obstante, no se evidencia una construcción teórica que asuma al videojuego como un discurso, es decir, que provenga desde el ámbito de la lingüística y desde una perspectiva multimodal. Knight (2015).…”
Section: Videojuego Como Discurso Digital: Aspectos Metodológicos Parunclassified
“…The researchers state that children like, accept, use, and are very motivated with the use of the certain software [11].…”
Section: Sensory and Physical Impairmentsmentioning
confidence: 99%
“…Researchers have created recreational digital games for traditional computers as well as various other hardware platforms [7,8,11,16,27,34,37]. McElligott et al [26] conducted co-design with blind children and developed several computer games with audio feedback.…”
Section: Accessible Digital Gamesmentioning
confidence: 99%
“…They found that children enjoyed playing their games individually and in groups, working together on challenging parts of the game. Sánchez et al [34] also developed an accessible game on a custom hardware platform called MOVA3D, which teaches children orientation and mobility skills. …”
Section: Educational Gamesmentioning
confidence: 99%